Anesthetic Management of Endovascular Treatment of Acute Ischemic Stroke During COVID-19 Pandemic: Consensus Statement From Society for Neuroscience in Anesthesiology & Critical Care (SNACC). Issue 3 (July 2020) - Sharma, Deepak; Rasmussen, Mads; Han, Ruquan; Whalin, Matthew K.; Davis, Melinda; Kofke, W. Andrew; Venkatraghvan, Lakshmikumar; Raychev, Radoslav; Fraser, Justin F.
Abstract : The pandemic of coronavirus disease 2019 (COVID-19) has unique implications for the anesthetic management of endovascular therapy for acute ischemic stroke. The Society for Neuroscience in Anesthesiology and Critical Care appointed a task force to provide timely, consensus-based expert recommendations using available evidence for the safe and effective anesthetic management of endovascular therapy for acute ischemic stroke during the COVID-19 pandemic. The goal of this consensus statement is to provide recommendations for anesthetic management considering the following (and they are): (1) optimal neurological outcomes for patients; (2) minimizing the risk for health care professionals, and (3) facilitating judicious use of resources while accounting for existing variability in care. It provides a framework for selecting the optimal anesthetic technique (general anesthesia or monitored anesthesia care) for a given patient and offers suggestions for best practices for anesthesia care during the pandemic. Institutions and health care providers are encouraged to adapt these recommendations to best suit local needs, considering existing practice standards and resource availability to ensure safety of patients and providers.